Human Resource Performance in Hospital: A Bibliometric Study - Azmilla Nurrachmalia Adha; Qurratul Aini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Along with the growth of modern technology, hospitals and other health organizations are undergoing significant changes. Improving their services to remain accessible and generate the highest potential profit is essential. As an asset of the organization, human resource plays a substantial part in this accomplishment. Multiple studies have demonstrated that human resource performance impacts organizational performance. This study aims to determine the trend in hospital human resource performance. Literature from the Scopus database from 2012 to 2022 will be studied as part of the research method. VOSviewer is used to generate the bibliometric mapping. A total of 1754 documents were found in the Scopus database, with the year 2022 having the most publications. The United States contributed the most publications among other countries, and medicine was the subject area that published the most. Through VOSviewer, the bibliometric network showed topics between articles and their relationships. Keyword quality was the most widely discussed, has the highest link strength, and firmly correlates with human resource performance in hospital.